Determination of Alcoholic Concentration in Four Different Home Brewed Alcoholic Beverages Using Gas Chromatography - Kaphle, Sushma; Acharya, Apurba; Shakya, Arbin; Aryal, Bijay (Nepal Journal of Health Sciences, 2022)
Introduction: Alcohol, one of the most commonly consumed beverages across the world is manufactured both industrially as well as locally in Nepal. The proportions of locally brewed alcoholic beverages are higher due to geographical variation as well as presence of a population with varied cultural background. Even though the industrially manufactured alcoholic beverages are quantified, the home brewed beverages usually are produced and consumed without quantification. These alcoholic beverages consist of various components such as ethanol, methanol, iso-propanol, iso-butanol and others, each component having different pharmacological properties.Objectives: To determine the alcoholic concentration (ethanol, methanol, iso-propanol and iso-butanol) of four different varieties of home brewed alcoholic beverages in Jumla district, Nepal.Methods: Probability random sampling method was used for sample collection and sampling. The samples were taken to Zest laboratory, Bhaktapur. The laboratory then analysed all four samples to determine the concentration of different alcohols using Gas Chromatography. Unknown concentrations of different alcohol in the sample were measured by injecting standard sample with known concentration.Results: The concentration of alcoholic components in four different home brewed alcoholic beverage samples weredetermined using gas chromatographywith ethanol concentrations being 14.209%v/v, 16.323%v/v, 11.473%v/v and 49.217%v/v. Contamination was not detected in any of the samples except for one sample which contaminated iso-butanol (0.063% v/v).Conclusion: Various alcoholic components are present in home brewed alcoholic beverages at varied concentration levels and quantification of these beverages is highly essential in order to prevent health hazards associated with these components.